POLITICAL TRANSITIONS IN EMERGENT DEMOCRACIES: A COMPARATIVE ANALYSIS OF ELECTORAL PROCESSES IN NIGERIA AND GHANA (1999-2004) - Ofuebe, C; Anierobi, K.C (University of Nigeria Journal of Political Economy, 2022)
Political transitions to engender democracy are the current trend in Africa. Implicit therein is the exigency of elections, requiring institutions for the implementation. Their performance determine the success or otherwise of democratic transitions. Ghana’s were more satisfactory and, therefore, the country had better democratic transition. Nigeria’s electoral institutions had been problematic, accounting for her political troubles in democratisation. Thus, the electoral institutions need strengthening to perform satisfactorily so that the electoral processes becomes wholly efficient and transparent in Nigeria and Ghana.